Ideas of Educating Growing Generation in the Pedagogical Heritage of Native Pedagogues-Humanists A.Makarenko and V.Sukhomlynskyi - Yuliya Baranetska (Pedagogical Discourse, 2013)
The article considers pedagogical ideas of outstanding native pedagogues innovators of XX century A.S.Makarenko and V.O.Sukhomlynskyi concerning education of growing generation. Particularly, A.S.Makarenko’s views on main tasks of family education that are actual for parents nowadays are investigated. Special attention in thearticle is paid to works of V.O.Sukhomlynskyi, concerning psychological, pedagogical and social aspects of child’s phenomenon, analized views of outstanding researcher concerning essence of children’s and teenager’s education, ways and means of educational influence; the main values of educational interaction between teacher and his pupils are identified.